The moderating role of self-control in the relationship between peer affiliation and adolescents antisocial behavior in Tehran, Iran - Mobarake, Roya Kavian; Juhari, Rumaya; Yaacob, Siti Nor; Esmaeili, Nooshin Sabour (Canadian Center of Science and Education, 2014)
This study aims to examine the moderating effect of self-control in the relationship between peer affiliation and antisocial behavior in a sample of 395 adolescents aged 13 to 18 years old in Tehran city in Iran. Inventory of Parent and Peer Attachment (IPPA; Armsden & Greenberg, 1987), Self-Control Scale (Grasmick et al., 1993) and modified of Antisocial Behavior scale (Dekovic, 1999) were utilized to measured peer affiliation, self-control and antisocial behavior, respectively. Results of this study indicated that peer affiliation was significantly related to antisocial behavior among adolescents. The findings of this study have important implications that address the moderating role of self-control in the relationship between peer affiliation and adolescent’s antisocial behavior.